GEOTEXTILE AND GEOMEMBRANE USAGE IN AN IRAQI SANDY GEOENVIRONMENT (Journal of Engineering, 2008)
The work in this research presents an experimental and a theoretical study to obtain the effect of using a low permeability geosynthetic material on the longitudinal and lateral coefficients of dispersion. This would have its effect on the contaminants migration through an isotropic, homogenous and saturated soil. The first stage of this research involves the study of the geosynthetic material and in calculating the longitudinal and lateral coefficients of dispersion for an Iraqi sandy soil by using an experimental set-up to simulate the processes. To investigate the effect of using a geosynethtic material on the dispersion coefficients, the test was conducted for each velocity that was used in the experimental work and as follows: without using the geosynethtic material first, and  by using the geosynthetic material as a base and a cover for the soil sample. The second stage of this research is interested in developing a numerical model able to simulate the contaminants dispersion phenomenon. To solve the two-dimensional advectiondispersion equation, a numerical model was derived using the finite element method. This numerical model was verified by comparing it with the analytical solution of one-dimensional dispersion. To study the effect of using a geosynethtic material on the contaminants dispersion through soil, a proposed field problem is tested.